Geotechnical characteristics of sensitive Leda clay at Canada test site in Gloucester, Ontario - Paul W. Mayne; Ethan Cargill; Bruce Miller (AIMS Geosciences, 2019)
In 1954, the Canadian Geotechnical Research Site No. 1 was established as a testing and experimentation site for the soft and highly sensitive Leda clays that were deposited within the now-drained Champlain Sea. The Gloucester test site has a shallow groundwater table taken as hydrostatic at 0.8 m and is underlain by a sequence of leached marine sediments that make-up the Leda clays and extend about 22 m below grade. Below that are dense glacial tills and limestone bedrock. Previous research studies at the site have included full-scale construction, monitoring, and instrumentation of shallow foundations, embankments, drilled shafts, and driven pilings. Recently, a series of in-situ tests in 2012 and 2014 included type 1 and 2 piezocone soundings, porewater dissipations, and both conventional downhole tests and continuous-interval shear wave velocity measurements have been undertaken. Selected results obtained from laboratory, in-situ testing, and geophysical tests over the past six decades are presented.